Population-level scale-up of surgery platforms for women's cancer care in low- and middle-income countries. (March 2016) - Parham, Groesbeck P.; Mwanahamuntu, Mulindi H.; Hicks, Michael L.; Henry-Tillman, Ronda; Chibwesha, Carla J.; Chinula, Lameck; Oneko, Olola Achieng; Murokora, Daniel; Sahasrabuddhe, Vikrant V.
Highlights: LMICs are facing an unprecedented rise in annual cancer incidence. We provide a conceptual framework for scale-up of surgical care for women's cancer. We emphasize identifying highest priority conditions that can be managed by resource-appropriate and sustainable interventions. Core-competencies-based training of local health workers for targeted skills-building is essential. Implementing services within a public health framework will ensure service integration and promote sustainability. Abstract: Surgery is a cornerstone of management of women's cancer care in low- and middle-income countries. As cancer incidence rates and disease burden rise rapidly even in the lowest income nations, the need for investing in surgical care platforms at all levels of the health system (primary health care clinics to tertiary hospitals) is being increasingly recognized. In this article, a conceptual framework for approaching scaling-up surgery platforms for women's cancer care in regions with least resources and substantial burden of disease is presented. A case is made for identifying highest priority conditions that can be managed by resource-appropriate and sustainable interventions. Core-competencies-based training of local health workers for targeted skills-building and utilizing innovative approaches to care delivery by harnessing and incorporating affordable technology for monitoring, outcomes evaluation and ongoing program adaptation are essential. Implementing surgical cancer care within a public health framework will help ensure services are integrated in a manner that strengthens health systems at all levels.